Testing the Determinants of Corruption from Multiple Theoretical Lenses: The Case of the U.S. States - Liu, Cheol; Chen, Can (KDI School of Public Policy and Management, 2020)
This article compares the determinants of public corruption from multiple theoretical lenses and then tests which ones are more effective in curbing public corruption in the context of the U.S. states. We find that the stringency of state tax and expenditure limits, fiscal transparency, voter turnout rates, unified Democratic control, divided control of state governments, political competitiveness, population with Scandinavian ancestry, and educational attainment are all significantly and negatively associated with the extent of public corruption. Compared with other approaches to curbing corruption (i.e., the lawyer’s approach, the businessman’s approach, and the economist’s approach), those that restrict public officials’ discretionary power and encourage educated citizens’ participation appear to be more effective in reducing corruption in the U.S. states.
Keywords: Corruption; Comparison of Multiple Theories; Determinants and Cures for Corruption